Opening the Door: Rethinking "Difficult Conversations" about Living and Dying with Dementia - Buchbinder, Mara (The Hastings Center report, 2024)
This essay looks closely at metaphors and other figures of speech that often feature in how Americans talk about dementia, becoming part of cultural narratives: shared stories that convey ideas and values, and also worries and fears. It uses approaches from literary studies to analyze how cultural narratives about dementia may surface in conversations with family members or health care professionals. This essay also draws on research on a notable social effect of legalizing medical aid in dying: patients may find it easier to bring up a range of concerns, regardless of whether they have any interest in hastening their own death. The essay proposes that health care professionals rethink an idea prominent within their own culture: that conversations about the end of a person's life are inherently difficult. This framing may make it hard for people facing dementia to bring up their concerns about what lies ahead. We suggest a different way to think about these conversations, using the metaphor of "opening the door" to represent inviting a patient to bring up issues of deepest concern.